Sorghum utilization in grain-based food products in China and Australia - Anita Stefoska-Needham; Sophie L. Marsano; Liyan Zhong; Thomas H. Roberts (PLoS ONE, 2026)
Sorghum consumption has potential health-promoting effects for consumers. This study identified sorghum-containing grain-based food products available in major supermarkets in China and Australia. A total of 1,692 products were audited in Shenzhen, China and Illawarra, Australia, in 2023/24. Breakfast cereals and snack bars were evaluated in both countries, while flours, pastas, and noodles were evaluated only in Australia. Information on ingredients, including the presence of sorghum, food format, brand, product name, wholegrain/gluten-free labelling was recorded. In China, sorghum was found in 4.3% (12/279) of breakfast cereals, with only 1/12 sorghum-containing breakfast cereals listed sorghum in the first position of the ingredient list. Sorghum was found in 2.0% (9/458) of snack bars and was listed as either ‘sorghum’ (n = 3) or ‘sorghum flour’ (n = 6). In Australia, sorghum was found in 22/356 (6.2%) breakfast cereals, 9/285 (3.2%) snack bars, and was absent from all flours, pastas, and noodles. Most sorghum-containing cereals were extruded (36.4%) and labelled gluten-free (16/22, 73%) or wholegrain (14/22, 64%). Sorghum-containing snack bars, notably oat-bake and muesli bars, were mostly made from sorghum flour and flakes. Sorghum appeared in the first position in the ingredient list in 2/22 (9.1%) of breakfast cereals, and in the third or higher position for all snack bars. Among the breakfast cereal and snack bar subcategories analyzed, there were no significant differences in sorghum utilization between China and Australia (Fisher’s Exact Tests, p < 0.05), except for oat bake snack bars (higher in China, p = 0.0265). Overall, the audit data suggests that sorghum is not widely incorporated as an ingredient in common grain-based food products available to consumers in major Chinese and Australian supermarkets. Greater awareness of its potential consumer health benefits is needed to drive utilization of sorghum grain in foods across different markets.